Bullying among Primary School Students: Prevalence and Correlates - Jaradat, Abdul-Kareem (Jordan Journal of Educational Sciences, 2008)
This study investigated the prevalence and correlates of bullying among a sample of 656 students in grades 7 to 10. Overall, 18.9% of participants were classified as bullies, 10.2% as victims, 1.5% as bully-victims, and 69.4% as neutral students. Calling names was the most common form of bullying used by bullies and experienced by victims. Males reported bullying their peers significantly more than females. Likewise, males reported more victimization than females. Sex differences also emerged in the locations of bullying. The most popular location of bullying for males was on the way home, while for females it was the classroom. Grade differences emerged with 7th and 8th graders indicating significantly more victimization than 9th and 10th graders. On the other hand, it was found that both neutral students and bullies had significantly higher self-esteem than did victims. Neutral students had significantly better family relationships than did victims, and they had higher academic performance than did bullies or victims. Implications for school-based prevention services are provided